WHO Mental Health Gap Action Programme (mhGAP) Intervention Guide: a systematic review of evidence from low and middle-income countries. Issue 1 (13th September 2017) - Keynejad, Roxanne C; Dua, Tarun; Barbui, Corrado; Thornicroft, Graham
Abstract : Question: Despite mental, neurological and substance use (MNS) disorders being highly prevalent, there is a worldwide gap between service need and provision. WHO launched its Mental Health Gap Action Programme (mhGAP) in 2008, and the Intervention Guide (mhGAP-IG) in 2010. mhGAP-IG provides evidence-based guidance and tools for assessment and integrated management of priority MNS disorders in low and middle-income countries (LMICs), using clinical decision-making protocols. It targets a non-specialised primary healthcare audience, but has also been used by ministries, non-governmental organisations and academics, for mental health service scale-up in 90 countries. This review aimed to identify evidence to date for mhGAP-IG implementation in LMICs. Study selection and analysis: We searched MEDLINE, Embase, PsycINFO, Web of Knowledge/Web of Science, Scopus, CINAHL, LILACS, SciELO/Web of Science, Cochrane, Pubmed databases and Google Scholar for studies reporting evidence, experience or evaluation of mhGAP-IG in LMICs, in any language. Data were extracted from included papers, but heterogeneity prevented meta-analysis. Findings: We conducted a systematic review of evidence to date, of mhGAP-IG implementation and evaluation in LMICs. Thirty-three included studies reported 15 training courses, 9 clinical implementations, 3 country contextualisations, 3 economic models, 2 uses as control interventions and 1 use to develop a rating scale. Our review identified the importance of detailed reports of contextual challenges in the field, alongside detailed protocols, qualitative studies and randomised controlled trials. Conclusions: The mhGAP-IG literature is substantial, relative to other published evaluations of clinical practice guidelines: an important contribution to a neglected field.